Intention to Seek Mental Health Treatment for Adolescent Girls: Comparison of Predictors in Mothers and Daughters. Issue 4 (18th June 2013) - Logsdon, M. Cynthia; Pinto, Melissa D.; LaJoie, A. Scott; Hertweck, Paige; Lynch, Tania; Flamini, Laura
Abstract : Problem: To examine predictors of intention to seek mental health treatment for adolescent girls in mothers and daughters. Methods: In this cross‐sectional study, mothers and adolescent daughters ( n = 71) completed measures of behavioral attitudes, subjective norms, perceived behavioral control, and intention to seek mental health treatment for the adolescent daughter. Findings: Behavioral attitude and perceived behavioral control predicted intention to seek mental health treatment among mothers. Behavioral attitude predicted intention among daughters. There were no associations between mothers and daughters on study variables. Conclusions: To promote shared decision making and engagement in mental health treatment, clinicians may target interventions to the mother's perceived behavioral control and behavioral attitudes of daughters and mothers. Based upon study results, clinicians should promote shared decision making and concordance between mothers and daughters on attitudes toward mental health treatment.